Wall to wall speaks - Mus, David, 1936- (Princeton series of contemporary poets., 1988)
Most of these poems first appeared in Poetry magazine in the decade from 1967-76 and quickly became underground classics. Brought together here--with more recent work--they reveal their coherence and their urgency. From "Blake's Seasons": "To Spring" My God! The morning buttonholed me and you, Young Spring, slid down the facets from its crystal-Linity; can you see us here, this earth mote, Now it unites millions' faces turned for you?The earth budges and peopled calls to itself, And swells with us and our echoes towards your Lucent enshrining; withdraw that consent just Once, come smooth and sharp to stand within our voice!Try rising with the sun as I have seen you So our breath may catch at your warmth, lapped and tamed In daily humbling; in dew and jewels embrace The wintered soil still wincing from its last loss. With your cherishing, deft hands, yourself, garnish Her naked force, with your tongue luster her skin; Then leave her flare with your bewildering flame, Whose clear flesh was bounded to abound in you. Originally published in 1988. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905